A Prospective Study of Adverse Drug Reactions in 1 Month–12 Years Old Pediatric Patients - Asawari Raut; Vijay Kalrao; Roja Rani; Ravi Kumar (Indonesian Journal of Clinical Pharmacy, 2015)
Adequate controlled clinical trials in pediatric population, especially in oncology and vaccinations are still insufficient due to ethical considerations. Certain conditions in children in general and in Indian  children in particular, suggested the need for Adverse Drug Reaction (ADR) monitoring. Thus this study was aimed to investigate the incidence of ADRs in pediatric populations. A prospective spontaneous reporting study was conducted over a period of six months from October 2012 to March 2013 in pediatric inpatients ward of Bharati Hospital in Pune. Reported ADRs were assessed for its causality by using WHO causality assessment scale, and its severity by using Hart wig Severity Scale. A total of 107 suspected ADRs were reported and evaluated from 54 patients, showing an overall incidence of 4.75%. Incidence rate of ADRs during hospitalization was 4.13%, while ADRs induced hospitalization was 0.62%. The gastrointestinal system (48.59%) was the most affected, and antibiotics was the most common the drug class associated to ADRs. In term of causality, 55.14% of the reactions were classified as possible, while in term of severity, 64.49% were classified as moderate. Most patients (60.75%) recovered from the incidence. Although the prevalence and severity of ADRs in pediatrics populations is reported to be higher than those of in adults, the incidence of ADRs in our study was only 4.75% which is lower than those of reported in adults, this may due to the spontaneous reporting system that used in this study.Keywords: Adverse drug reaction, causality, prospective spontaneous reporting system, severity Studi Prospektif Reaksi Obat yang Merugikan pada Pasien Anak 1 Bulan–12 TahunUji klinik pada anak khususnya onkologi dan vaksinasi masih kurang memadai karena pertimbangan aspek etik. Kondisi tertentu pada anak secara umum dan khususnya di India memerlukan pemantauan Rekasi Obat yang Merugikan (ROM). Penelitian ini bertujuan untuk mengetahui insidensi ROM pada pasien anak. Studi pelaporan spontan prospektif dilakukan selama enam bulan pada Oktober 2012–Maret 2013 di bangsal anak Rumah Sakit Bharati di Pune. ROM yang dilaporkan dinilai kausalitasnya dengan WHO causality assessment dan keparahan dengan skala Wig Hart Severity. Sebanyak 107 suspek ROM dilaporkan dan dievaluasi dari 54 pasien menunjukkan insidensi sebesar 4,75%. Tingkat kejadian ROM selama rawat inap sebesar 4,13% sementara ROM yang menyebabkan pasien dirawat inap sebesar 0,61%. Sistem pencernaan (48,5%) paling sering dilaporkan dan antibiotik sebagai obat yang berasosiasi dengan ROM. Berdasarkan kausalitas, 55,14% reaksi obat diklasifikasikan possible (55,14%) sementara dalam aspek kepaharahan, 64,49% diklasifikasikan moderat. Mayoritas pasien sembuh dari ROM (60,75%). Prevalensi dan keparahan ROM pada anak dilaporkan lebih tinggi dibandingkan dewasa, akan tetapi insiden ROM pada penelitian ini hanya 4,75% yang lebih rendah daripada yang dilaporkan pada orang dewasa, dimungkinkan karena penelitian ini merupakan sistem pelaporan spontan.Kata kunci: Causality, keparahan, reaksi obat yang merugikan, sistem pelaporan spontan prospektif